Advantages and Disadvantages of Living and the Needs of Local Residents in Svečina, Turnišče, and Cirkulane - Žagavec, Aljaž; Pucko, Klemen; Jöbstl, Gita; Kumer, Peter (Journal for Geography, 2023)
This study addresses the perceptions and needs of local residents in three rural areas. It compares the opinions of the residents with the strategic plans previously adopted by Local Action Groups and Regional Development Agencies. The results highlight the differences and similarities between the views of the local population and the strategic plans, prompting a discussion on the effectiveness and direction of regional development.
Keywords: rural development; regional policy; community needs; local perceptions; strategic planning; qualitative analysis; rural Slovenia